A charge integrator amplifier and trap detector for pico-joule laser pulse energy measurement. (10th August 2018) - White, M G; Porrovecchio, G; Livigni, D; Leonhardt, R; Smid, M
Abstract: We report the characterisation and calibration of a new laser pulse energy measurement device, developed for pico-joule pulse energy measurement at repetition rates up to 1 kHz. The device comprises a charge integration amplifier operating in conjunction with an input charge source; a light trapping photo-detector, which converts an incident laser pulse to a charge pulse. The novel amplifier individually integrates each charge pulse from the source and outputs a corresponding 20-bit resolution digital signal. This signal is converted to pulse energy through post processing, knowing the absolute responsivity of the photodiode detector and the calibration factors of the charge amplifier. A differential evolution algorithm is used to determine optimised values for the feedback capacitors of the amplifier, the amplifier gain and offset. The values measured by the new laser pulse energy meter were compared with those obtained from measurements traceable to both the high and low-level laser pulse energy scales maintained by NIST, Boulder. These were consistent within the combined expanded measurement uncertainty. This new device offers lower uncertainty and portability, suitable for field use.